Knowledge about continuous positive airway pressure machine usage among nurses at a tertiary hospital in Tanzania - Wilson Paulo Lomnyack; Tumbwene Mwansisya; Stewart Mbelwa; Kahabi Isangula; Zephania Saitabau Abraham (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2020)
Introduction: Continuous Positive Airway Pressure (CPAP) provides an air pressure that maintains the patency of the airway in patients with a variety of breathing problems. Nurses provide the hour to hour management of patients who require CPAP. The aim of this study was to assess the knowledge of nurses about CPAP machine usage at the tertiary hospital in Tanzania which serves the largest number of patients who require CPAP. Method: A hospital-based descriptive cross-sectional study was carried out from March to June 2019 at Muhimbili National Hospital (MNH) and Jakaya Kikwete Cardiac Institute (JKCI) where 149 nurses who consented to participate were recruited. Data were collected using structured questionnaires and analysed using a statistical package for social sciences (SPSS) version 20. P-value<0.05 was considered to be statistically significant. Results: Of the149 nurses recruited 80(53.7%) were female and 69 (46.3%) were male; 99 (66.4.%) were aged 26-35 years; 78 (52.3%) had a diploma in nursing as the highest level of education and 138 (93.9%) had work experience of less than ten years. Forty five percent of nurses had moderate knowledge about CPAP machine usage. High and moderate level of knowledge among nurses about CPAP general information each equally accounted for 38.9% and poor level of knowledge accounted for 2.7%. Moreover, moderate level of knowledge about CPAP device contraindications accounted for 43% whilst poor knowledge attributed 8.7%. There was no significant association between nurses' knowledge and their socio-demographic characteristics. Conclusion: Just under half of the nurses had moderate knowledge of CPAP device use and most of them had attended only a single training session on CPAP device use and the range of time from training until completing questionnaires was at least six months. Regular training on CPAP machine usage should be provided to nurses since they are in the front line in management of patients requiring CPAP.